Multi-lens analysis of LMS feature adoption in higher education - Ubaidah, Ubaidah; Budiono, Tri Asih; Darmadi, Herru; Sukmono, Ailsa Naurah (Frontiers in Education, 2026)
IntroductionThis study investigates how university lecturers adopt Learning Management System (LMS) features, focusing on innovation attributes, psychological-emotional influences in the adoption process (knowledge, persuasion, decision, implementation, and confirmation), and the role of higher education as a social system.MethodThis study applies a qualitative approach by using Rogers' Diffusion of Innovations (DOI) framework, and qualitative data from focus group discussions (FGD). FGD was conducted with lecturers, staff, and students, and was analyzed through three lenses: innovation attributes (relative advantage, compatibility, complexity, trialability, and observability), emotional factors in the adoption process, and social-environmental influences (e.g., institutional policy, peer norms, student expectations). Data was collected from three focus group discussions (FGDs) with lecturers and students, and triangulated with LMS system usage logs capturing assessment feature usage over five semesters.ResultThe findings reveal that adoption is not solely determined by feature functionality but also by emotional readiness and social-cultural contexts. A total of 104 references were identified and coded. Complexity emerged as the most frequent barrier (35 codes), followed by compatibility (23) and relative advantage (24). Emotional factors were prominent: anxiety (18 mentions) and avoidance (9) shaped late adopters' hesitation, while confidence (11) distinguished early adopters. Late adopters referenced the confirmation stage almost twice as often (11 vs. 6), reflecting a stronger need for reassurance. While early adopters engage LMS features with confidence and curiosity, late adopters are usually hindered by complexity, anxiety, and a lack of support. Institutional mandates and peer modeling encourage diffusion, but departmental inconsistencies create barriers.ConclusionIt suggests that successful LMS integration requires more than training and tools; it demands emotional scaffolding, culturally responsive leadership, and multi-level stakeholder engagement. The findings offer actionable guidance for LMS developers and higher education institutions to create and maintain sustained and inclusive digital learning environments.